Speech Based Anti Stuttering Algorithm using Matlab - Prabhu, R.; Kumar, P. Praveen; kumar, J. Kavin; L., Dhivyapriya E. (International journal of engineering and advanced technology, 2020)
Stuttering is one of the most occurring speech disorders. Usual onset of stuttering is from 2 to 5 years which can be cured in childhood but for 20% of cases it prolongs to adulthood. Its severity increases when a stuttered person faces public and when he/she gets anxious. It is a long-term disorder which cannot be permanently cured. This drawback will be externally overcome with the help of designed Speech based algorithm. This algorithm is implemented in five stages namely magnitude filtering, silence ejection, speech to text, repetition removal and text to speech (TTS). The project aims at removing the repetition of words. This can be used in speech recognition systems. This system helps in encouraging the person who suffers from stuttering to give an open talk in public.